The Haunted Showboat - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1957)
Nancy, Bess, and George travel to New Orleans during Mardi Gras to help restore an old, "haunted" showboat named the River Princess. Amidst threats, sabotage, and supposed ghost sightings, Nancy uncovers a plot involving counterfeiters and hidden pirate treasure.
Keywords: The plot centers on Nancy, Bess, and George traveling to New Orleans during Mardi Gras to help relatives solve a mystery involving an old, abandoned showboat named the River Princess; mystery series, revolves around themes of restoring heritage, bravery, and navigating personal relationships, particularly focusing on the idea that appearances can be misleading